Colloidal Core–Satellite Supraparticles via Preprogramed Burst of Nanostructured Micro-Raspberry Particles - Stauch, Claudia; Hobbs, Christopher; Shmeliov, Aleksey; Nicolosi, Valeria; Ballweg, Thomas; Luxenhofer, Robert; Mandel, Karl (Particle & Particle Systems Characterization, 2018)
Colloidal molecules, or more general supraparticles, i.e., particles which are themselves assembled of smaller nanoparticles in a defined way, are known to be synthesizable via bottom-up assembly techniques in colloidal dispersion. The amount of synthesizable particles is mostly limited to milligrams. Herein, a bottom-up-programed, triggerable top-down process is reported to obtain core–satellite supraparticles, i.e., particles composed of a larger core particle surrounded by smaller satellite particles. The key is to prepare a nanostructured, microparticulate powder into which defined burst behavior is preprogramed. Once the system is mechanically triggered, it bursts into well-defined nanosized core–satellite supraparticles. Scale-up is easily feasible and several hundred grams per batch can be demonstrated. The product is a ready-to-use and flexibly processible powder. Upon simple mixing with a polymer, it disintegrates into the preprogramed core–satellite supraparticles, thus forming a highly sophisticated nanocomposite with the polymer matrix. A pure silica nanoparticle system and a silica–iron oxide nanoparticle hybrid system are presented to demonstrate the versatility of the approach. Enhanced mechanical and unexpected magneto-optical properties with the particle system are found. The disintegration of the microparticles into individual core–satellite colloidal supraparticles is confirmed via in situ liquid cell transmission electron microscopy.
CRIS-Team Scopus Importer:2020-04-02
Keywords: core–satellite particles; nanostructured microparticles; raspberry particles; redispersible nanoparticles; supraparticles